2006
DOI: 10.1093/jn/136.6.1716s
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Toxicity Biomarkers for Methionine Excess in Rats

Abstract: Although many animal studies have reported that dietary excess of methionine causes toxic changes including growth suppression and hemolytic anemia, the biochemical mechanism and biomarkers for methionine toxicity have not been well elucidated. The present study aimed to identify toxicity biomarkers from plasma metabolites in rats fed excessive methionine. Young growing rats were fed graded doses of additional methionine for 2 wk. Cluster analysis of multivariate correlations was performed on the physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 28 publications
4
45
0
Order By: Relevance
“…The study had several limitations. Although the mean HCY concentration in the methionine group was similar to that reported by others (17 ) (27.3 vs 25.3 mol/L), excessive methionine supplementation in rats is known to have toxic effects, such as hemolytic anemia and growth suppression (18 ). HCY appears to be among the most plausible explanations for these toxic effects (18 ), but it is possible that methionine-induced effects might reflect systemic toxicity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The study had several limitations. Although the mean HCY concentration in the methionine group was similar to that reported by others (17 ) (27.3 vs 25.3 mol/L), excessive methionine supplementation in rats is known to have toxic effects, such as hemolytic anemia and growth suppression (18 ). HCY appears to be among the most plausible explanations for these toxic effects (18 ), but it is possible that methionine-induced effects might reflect systemic toxicity.…”
Section: Discussionsupporting
confidence: 85%
“…Although the mean HCY concentration in the methionine group was similar to that reported by others (17 ) (27.3 vs 25.3 mol/L), excessive methionine supplementation in rats is known to have toxic effects, such as hemolytic anemia and growth suppression (18 ). HCY appears to be among the most plausible explanations for these toxic effects (18 ), but it is possible that methionine-induced effects might reflect systemic toxicity. We thus substantiated our observations by another, biochemically different model of HHCY consisting of a homocystine-enriched diet, and achieved mean HCY concentrations similar to those reported by Joseph et al (19 ), who used a 9 g/kg homocystine diet.…”
Section: Discussionsupporting
confidence: 85%
“…KMTB is then oxidatively decarboxylated to 3-methylthiopropionate (MTP) through an irreversible reaction catalyzed by the branched chain 2-oxo acid dehydrogenase complex (BCKDC) (15). MTP is further metabolized to the gaseous methanethiol (16), which has been reported to then be broken down into simpler molecules, including hydrogen sulfide, dimethyl sulfide, and formic acid, with the end products being carbon dioxide and sulfur dioxide (17,18). Although initial reports on methionine transamination suggested that it provides a route for the degradation and clearance of methionine (19), more recently researchers have claimed that transsulfuration serves as the major pathway for the detoxification of excessive methionine (20).…”
mentioning
confidence: 99%
“…On the other hand, diet supplementation with low doses of methionine (0.2%, 0.3%, 0.4% feed weight) favored increased feed intake and animal growth [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%